Conformal Pickering emulsion graphene coatings for electrode materials, methods of formation and uses thereof

The coating of graphene in lithium-ion batteries through Pickering emulsification method solves the problem of excessive limiting of electrochemical performance of inactive components, and achieves efficient electron and lithium ion transportation, significantly improving the specific and volume capacity of the battery.

JP7654690B2Active Publication Date: 2025-04-01NORTHWESTERN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2022567153
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-05-04
Filing Date
2021-04-22
Publication Date
2025-04-01
Estimated Expiration
2041-04-22

AI Technical Summary

Technical Problem

Excessive inactive components exist in existing lithium-ion batteries, limiting the electrochemical properties of the battery, especially when reducing conductive additives.

Method used

The conductive graphene coating was prepared by Pickering emulsification method, and the graphene was emulsified and dropped onto the active material particles to achieve an efficient and uniform coating of graphene.

Benefits of technology

It has achieved efficient electron and lithium ion transportation at extremely low conductive additive levels, significantly improving the specific and volume capacity of the battery, reaching more than 98% of the theoretical limit of active materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007654690000004
    Figure 0007654690000004
  • Figure 0007654690000005
    Figure 0007654690000005
  • Figure 0007654690000006
    Figure 0007654690000006
Patent Text Reader

Abstract

A method for producing a composite material includes forming an emulsion mixture of active material particles and graphene emulsion droplets containing immiscible first and second solvents and a solid-state emulsifier for graphene, where the first and second solvents are adapted such that the first solvent is an external solvent and the second solvent is present inside the graphene emulsion droplets and the active material particles are present inside the emulsion droplets, and the boiling point of the second solvent is lower than the boiling point of the first solvent; drying the emulsion mixture, followed by evaporating the second solvent and the first solvent by fractional distillation to form a composite material in which each surface of the active material particles is conformally coated with the graphene.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Statement of Rights Under Federally Sponsored Research This invention was made with Government support under Grants CMMI-1727846 and DMR-1720139 awarded by the National Science Foundation, and DEAC02-06CH1157 awarded by the Department of Energy. The Government has certain rights in this invention.

[0002] CROSS-REFERENCE TO RELATED PATENT APPLICATIONS This application claims priority to and the benefit of U.S. Provisional Application No. 63 / 019,552, filed May 4, 2020, which is incorporated by reference in its entirety.

[0003] The present invention relates generally to materials, and more particularly to conformal Pickering emulsion graphene coatings for electrode materials, methods of formation and applications thereof. [Background technology]

[0004] The description of the background art provided herein is intended to generally present the context of the present invention. It should not be assumed that the subject matter discussed in the Background of the Invention is prior art merely because it is mentioned in the Background of the Invention. Similarly, it should not be assumed that the problems mentioned in the Background of the Invention or related to the subject matter of the Background of the Invention have been previously recognized in the prior art. The subject matter in the Background of the Invention merely represents different approaches and may be inventions in their own right. The work of the inventors cited herein, to the extent described in the Background of the Invention, as well as aspects of the specification that may not otherwise qualify as prior art at the time of filing, are not admitted, expressly or impliedly, as prior art against the present invention.

[0005] As confirmed by the 2019 Nobel Prize in Chemistry, lithium-ion batteries (LIBs) have become ubiquitous and have had a major impact on a variety of technologies, including portable electronics, electric vehicles, home energy storage systems, and grid-level energy leveling solutions. The main feature of rechargeable LIBs is their high energy and power density, which stems from their reversible and efficient electrochemistry. However, the growing demand for increased range in electric vehicles and battery life in portable devices is driving efforts to develop next-generation LIBs with greater capacity. As the capacity of a LIB is primarily determined by its electrochemically active electrode material, a significant number of studies have attempted to identify alternative materials with greater reversible lithiation capacity. In particular, high-capacity cathode materials have been intensively investigated, as cathode materials generally exhibit significantly lower capacity than anode materials, leaving more room for improvement. The capacity of an active electrode material is quantified by two figures of merit: capacity per unit mass (i.e., mAh g -1 Capacity per unit volume (i.e., mAh, cc) and capacity per unit volume (i.e., specific capacity or gravimetric capacity, with typical units of -1 (Volumetric capacity has typical units of 1000 kcal / s). Until now, high specific capacitance has been the target for electronic devices to enable improved portability. However, for large-scale applications such as electric vehicles and home energy storage systems, high volumetric capacity is equally important due to the limited space in which large LIB packs can be placed.

[0006] The practical specific and volumetric capacity of Li-ion batteries depends not only on the intrinsic properties of the active materials but also heavily on the content of other inactive components in the electrodes. Thus, Li-ion batteries exhibit practical capacities 5-20% below the theoretical limit due to the inactive components. To achieve the high energy densities required by emerging technologies, Li-ion battery electrodes must approach the volumetric and specific capacity limits of their electrochemically active components, which requires minimizing the inactive components in the electrodes. However, reducing the proportion of inactive conductive additives limits the charge transport in the battery electrodes, thereby compromising the electrochemical performance.

[0007] Thus, a heretofore undescribed need exists in the art to address the aforementioned shortcomings and deficiencies. Summary of the Invention [Problem to be solved by the invention]

[0008] One of the objectives of the present invention is to provide composite materials and composite electrodes that provide efficient electron and lithium ion transport kinetics at exceptionally low conductive additive levels and commercially relevant active material surface loadings. [Means for solving the problem]

[0009] In one aspect, the present invention relates to a method for producing a composite material, comprising forming an emulsion mixture of active material particles and graphene emulsion droplets containing immiscible first and second solvents and a graphene solid state emulsifier, the first and second solvents being adapted such that the first solvent is an external solvent and the second solvent is present inside the graphene emulsion droplets and the active material particles are present inside the emulsion droplets, the boiling point of the second solvent being lower than the boiling point of the first solvent, drying the emulsion mixture, followed by evaporating the second solvent and the first solvent by fractional distillation to form a composite material in which each surface of the active material particles is conformally coated with the graphene.

[0010] In one embodiment, the step of forming an emulsion mixture includes dispersing the graphene in a first solvent to form a base solution, mixing a second solvent with the base solution to form graphene emulsion droplets by sonication, and inserting active material particles into the graphene emulsion droplets by agitation.

[0011] In another embodiment, the step of forming an emulsion mixture includes dispersing the graphene in a first solvent to form a base solution, dispersing active material particles in the base solution to form a first mixture, adding a second solvent to the first mixture to form a second mixture, and sonicating the second mixture to intercalate the active material particles into the graphene emulsion droplets.

[0012] In one embodiment, the graphene emulsion droplets further contain ethyl cellulose (EC) as an additive to enhance the dispersibility and emulsifier properties of the graphene.

[0013] In one embodiment, the mass ratio of the graphene to the EC ranges from about 1:0 to about 1:3, preferably about 1:2.

[0014] In one embodiment, the method further comprises thermally annealing the composite material in an oxidizing environment at a temperature to decompose most of the EC, leaving the remaining amorphous carbon residue with high sp 2 In one embodiment, the temperature is in the range of about 150-350°C, preferably about 250°C.

[0015] In one embodiment, the average size of the graphene emulsion droplets is varied by varying the volume ratio of a first solvent to a second solvent and the concentration of the graphene in the base solution.

[0016] In one embodiment, the volume ratio of the first solvent to the second solvent ranges from about 5:4 to about 5:1.

[0017] In one embodiment, the average size of the graphene emulsion droplets decreases as the content of the second solvent decreases, and is less than about 5 μm at a volume ratio of first solvent to second solvent of 5:1.

[0018] In one embodiment, the first solvent comprises acetonitrile, heptane, water, or acetic acid, and the second solvent comprises pentane, cyclohexane, acetonitrile, benzene, hexane, or chloroform.

[0019] In one embodiment, the first solvent comprises acetonitrile, which has a boiling point of 82°C, and the second solvent comprises hexane, which has a boiling point of 68°C.

[0020] In one embodiment, fractional distillation is carried out in a rotary evaporator with a bath temperature set at about 50° C. and a pressure set at about 0.6 atm for a first period of time to completely and selectively remove the hexane, thereby resulting in controlled collapse of the emulsion droplets and conformal graphene coating on the active material particles, and subsequently the pressure is reduced to below 0.2 atm for a second period of time to completely remove the acetonitrile, thereby resulting in conformal graphene-coated active material particles.

[0021] In one embodiment, the weight ratio of the graphene to the active material particles is in the range of about 1:400 to about 1:100, preferably about 1:200.

[0022] In one embodiment, the graphene comprises solution exfoliated graphene.

[0023] In one embodiment, the active material includes lithium cobalt oxide, lithium iron phosphate, lithium manganese oxide, lithium nickel manganese cobalt oxide, lithium nickel cobalt aluminum oxide, or combinations thereof.

[0024] In one embodiment, the active material includes nickel-rich lithium oxide.

[0025] In one embodiment, the active material is LiNi 0.8 Co 0.15 Al 0.05 O 2 (NCA), LiNiO 2 (LNO), LiMn 1.5 Ni 0.5 O 4 (LMNO), LiNi x Mn y Co z O 2 (NMC, in the formula, x+y+z=1), LiNi 0.8 Co 0.2 O 2 (LNCO), or Li w Ni x Mn y Co z O 2 (lithium-rich NMC, where w>1 and x+y+z=1).

[0026] In one embodiment, the active material is doped with elements including Al, B, Zr, Nb, Fe, Cr, Cu, Mo, W, and / or V.

[0027] In another aspect, the present invention relates to a composite material comprising graphene and active material particles, wherein each surface of the active material particles is conformally coated with said graphene.

[0028] In one embodiment, each of said surfaces of the active material particles is conformally coated with said graphene by a Pickering emulsion process.

[0029] In one embodiment, the composite material comprises sp 2 , which facilitates electron transport between the graphene flakes. 2 The method further comprises the steps of: providing a carbon content of amorphous carbon, hi one embodiment, the amorphous carbon is an annealing product of ethyl cellulose.

[0030] In one embodiment, the weight ratio of the graphene to the active material particles is in the range of about 1:400 to about 1:100, preferably about 1:200.

[0031] In one embodiment, the graphene comprises solution exfoliated graphene.

[0032] In one embodiment, the active material includes lithium cobalt oxide, lithium iron phosphate, lithium manganese oxide, lithium nickel manganese cobalt oxide, lithium nickel cobalt aluminum oxide, or combinations thereof.

[0033] In one embodiment, the active material includes nickel-rich lithium oxide.

[0034] In one embodiment, the active material comprises NCA, LNO, LMNO, NMC, LNCO, or lithium-rich NMC.

[0035] In one embodiment, the active material is doped with elements including Al, B, Zr, Nb, Fe, Cr, Cu, Mo, W, and / or V.

[0036] In yet another aspect, the present invention relates to an electrode for an electrochemical device comprising graphene and active material particles, the electrode comprising a composite material in which each surface of the active material particles is conformally coated with said graphene.

[0037] In one embodiment, the composite material comprises sp 2 , which facilitates electron transport between the graphene flakes. 2 The method further comprises the steps of: providing a carbon content of amorphous carbon, hi one embodiment, the amorphous carbon is an annealing product of ethyl cellulose.

[0038] In one embodiment, each of said surfaces of the active material particles is conformally coated with said graphene by a Pickering emulsion process.

[0039] In one embodiment, the weight ratio of the graphene to the active material particles is in the range of about 1:400 to about 1:100, preferably about 1:200.

[0040] In one embodiment, the graphene comprises solution exfoliated graphene.

[0041] In one embodiment, the active material includes lithium cobalt oxide, lithium iron phosphate, lithium manganese oxide, lithium nickel manganese cobalt oxide, lithium nickel cobalt aluminum oxide, or combinations thereof.

[0042] In one embodiment, the active material includes nickel-rich lithium oxide.

[0043] In one embodiment, the active material comprises NCA, LNO, LMNO, NMC, LNCO, or lithium-rich NMC.

[0044] In one embodiment, the active material is doped with elements including Al, B, Zr, Nb, Fe, Cr, Cu, Mo, W, and / or V.

[0045] In one embodiment, an electrode having as little as 0.5% by weight of graphene has a graphene density of about 10 mg cm -2 The present invention achieves greater than 100% active material surface loading, as well as volumetric and specific capacitances that are at least about 98% of the theoretical limits of the active materials.

[0046] In one embodiment, an electrode with as little as 0.5% by weight graphene retains about 91.5% of its initial volumetric capacity over 100 cycles and maintains a coulombic efficiency of about 99.7%.

[0047] In one embodiment, an electrode with as little as 0.5% by weight graphene retains about 70% of its initial volumetric capacity over 250 cycles.

[0048] An aspect of the present invention also relates to an electrochemical device comprising an electrode as disclosed above.

[0049] In one embodiment, the electrochemical device is a battery.

[0050] These and other aspects of the invention will become apparent from the following description of the preferred embodiments taken in conjunction with the following drawings, in which modification and variations may be effected without departing from the spirit and scope of the novel concepts of the disclosure.

[0051] The accompanying drawings illustrate one or more embodiments of the invention and, together with the written description, serve to explain the principles of the invention. Wherever possible, the same reference numbers are used throughout the drawings to refer to the same or like elements of the embodiments. [Brief description of the drawings]

[0052] [Figure 1A] 1A-1D show a comparison of point contact and conformal planar contact charge transport networks in lithium ion battery electrodes: Figure 1A: Schematic of a conventional electrode consisting of active material and carbon black conductive agent. [Figure 1B] The inherently restricted point-contact electron transport pathways resulting from the particle-based carbon additive. [Figure 1C] 1 is an electrode including thin graphene coated active particles with high packing density according to an embodiment of the present invention. [Figure 1D]Conformal planar contact minimizes current bottlenecks and facilitates permeation paths across the electrodes according to embodiments of the present invention. [Figure 2A] 2A-2G show graphene Pickering emulsions based on acetonitrile and hexane, according to embodiments of the present invention: Figure 2A: Schematic of Gr / EC Pickering emulsion in acetonitrile and hexane followed by intercalation of active material particles. [Figure 2B] Dispersion behavior of graphene in acetonitrile as a function of the Gr:EC (w / w) ratio. The inset shows a magnified image of the dispersion quality. [Figure 2C] 1A-1C are atomic force microscope images of pristine graphene flakes obtained by liquid-phase exfoliation. [Figure 2D] Hexane droplets formed in Gr / EC / acetonitrile solutions with volume ratios of acetonitrile to hexane of (left to right) 5:4, 5:3, 5:2, and 5:1. The graphene concentration in acetonitrile is fixed at 0.275 mg cc-1. [Figure 2E] 4. Size change of emulsion droplets with changing volume ratio of hexane to acetonitrile. [Figure 2F] Encapsulation of NCA active particles by emulsion droplets with volume ratios of acetonitrile to hexane of (left to right) 5:3, 5:2, and 5:1, and graphene concentration in acetonitrile of 0.275 mg cc-1. The graphene to NCA mass ratio is 1:200. [Figure 2G] Magnified optical microscope images of encapsulated NCA particles at (left) 5:3 and (right) 5:1 acetonitrile to hexane ratios. [Figure 3A] 3A-3H show high graphene coverage uniformity by fractional distillation according to embodiments of the present invention: Figure 3A: Schematic comparison of coverage uniformity as a function of drying process: (left) normal drying process and (right) fractional distillation drying process by sequentially evaporating hexane and acetonitrile. [Figure 3B]1 is an optical microscope image of a conventional process dried powder. [Figure 3C] 1 is an optical microscope image of dried powder using fractional distillation. [Figure 3D] Chamber pressure as a function of time during fractional distillation. The heating bath is set at 50° C. [Figure 3E] 1 is a scanning electron microscope image showing the bare active material surface. [Figure 3F] 13 is a scanning electron microscope image showing NCA particles prepared by a single solvent process using Gr / EC dispersed in acetonitrile with normal drying on a hot plate at 50° C. [Figure 3G] 1 is a scanning electron microscope image showing NCA particles prepared by the Pickering emulsion process with normal drying on a hot plate at 50° C. [Figure 3H] 1 is a scanning electron microscope image showing NCA particles prepared by the Pickering emulsion process with drying by fractional distillation. [Figure 4A] 4A-4F show scaled-up coating and characterization after ethylcellulose removal according to embodiments of the present invention. Figure 4A: Scaled-up Pickering emulsion process for conformally coating 10 g of NCA powder with graphene. [Figure 4B] 4 shows Raman spectra of the coated powder and bare NCA before removal of the ethyl cellulose, after removal of the ethyl cellulose by thermal annealing at about 250° C. in an oxidizing environment. [Figure 4C] Transmission electron microscope image of graphene encapsulated NCA particles revealing conformal graphene flakes / coatings on the surface of the NCA particles. [Figure 4D] 1 is a scanning electron microscope (SEM) image of a graphene encapsulated particle. [Figure 4E] 1 is a magnified SEM image showing the morphology of the coating. [Figure 4F]13 shows the energy dispersive spectroscopy results for O, Co, Ni, Al, and C elements on graphene-coated NCA particles after removal of ethyl cellulose. [Figure 5A] 5A-5G show electrochemical testing of NCA electrodes according to embodiments of the invention: Fig. 5A: Compressed thickness of electrodes consisting of 0.5 wt% graphene (left), 0.5 wt% carbon black (middle), and 5 wt% carbon black (right) electrodes. [Figure 5B] 1 is a top-view scanning electron microscope image of an electrode with 0.5% by weight graphene and 5% by weight carbon black. [Figure 5C] FIG. 2 shows the Nyquist plot of the prepared electrodes. [Figure 5D] Figure 10 shows the galvanostatic profile of the prepared electrode in terms of total electrode specific capacity at a current density of C / 10. A constant voltage of 2.8 V was applied after discharge until the current density reached C / 50. [Figure 5E] Rate capability results in terms of volumetric capacity. The electrodes were charged to 4.3 V at 1 C rate and discharged to 2.8 V at 1 C, 2 C, 5 C, and 10 C rates (except for the C / 10 test). [Figure 5F] Rate capability results in terms of total electrode specific capacity. [Figure 5G] This is the result of a cycle life test at a rate of 1C. [Figure 6A] Figures 6A-6C show a comparison of volumetric and specific capacitances with theoretical limits and prior literature. Figure 6A: The volumetric and specific capacitances of this study are compared to the theoretical limits (star dots) and prior literature (round dots) for various cathode materials. The references are defined as follows: Ref. [1] used a Mn content control, Ref. [2] used Al gradient doping, Ref. [3] used a grain growth control, Ref. [4] used a pre-oxidized precursor, Ref. [5] used a vanadium treatment, Ref. [6] used a NaAlO2 treatment, and Ref. [7] used a morphology control. For references that do not provide compaction / packing density, the density was estimated based on the amount of conductive carbon additive and binder used. [Figure 6B]1 is a comparison of rate performance results with prior art for volumetric capacity. [Figure 6C] 1 is a comparison of rate performance results with prior art for specific capacity. [Figure 7A] Photographs of NCA particles mixed in various solvents and stored for one week, according to an embodiment of the present invention. [Figure 7B] Figure 1 shows the X-ray diffraction patterns of dried particles after 1 week of storage. X-ray diffraction (XRD) patterns were measured with Cu-Kα radiation (λ = 1.5406 Å) using a Scintag. The accelerating voltage was 40 kV with a current of 20 mA. The patterns were collected in 2θ scan mode from 10 to 70°. No significant changes were observed in the XRD patterns. [Figure 8] 1 shows scanning electron microscope (SEM) images of NCA particles after one week of storage in the listed solvents, according to an embodiment of the present invention. Although there was no significant change in the X-ray diffraction pattern for any of these solvents, impurities were observed on the surface of NCA particles stored in ethanol, water, and acetone. No surface changes were observed for NCA particles stored in IPA, acetonitrile, and hexane. [Figure 9A] 9A and 9B show that graphene flakes were liquid-phase exfoliated from bulk graphite using an in-line shear mixer according to an embodiment of the invention. The flakes have an average thickness of 2.91 nm and an average lateral size of 156 nm. FIG. 9A: Atomic force microscope image of drop-cast graphene flakes. [Figure 9B] 1 is a histogram of graphene flake thickness. [Figure 10] FIG. 1 shows high resolution optical microscope images showing emulsion droplet size at a 5:1 ratio of acetonitrile to hexane, according to an embodiment of the present invention. [Figure 11]FIG. 1 shows optical microscope images for acetonitrile to hexane (A / H) ratios of 5:0.8, 5:0.6, 5:0.4, and 5:0.2 (left to right) according to an embodiment of the present invention. No significant change in emulsion droplet size was observed above acetonitrile to hexane ratios of 5:1. Instead, emulsion droplets tend to cluster at these low hexane levels (red circles). As a result, it was concluded that the limit for forming well-behaved emulsions is an acetonitrile to hexane ratio of 5:1. [Figure 12] Figure 1 shows the change in emulsion droplet size as a function of graphene concentration according to an embodiment of the present invention. No droplets were formed in samples a-b. From the optical microscope images, it was observed that the higher the concentration of graphene, the smaller the emulsion droplet size (samples c-h). Throughout this figure, the mass ratio of graphene to EC was kept constant at 1:2, and the volume ratio of acetonitrile to hexane was kept constant at 1:1. [Figure 13A] FIG. 1 shows an SEM image of NCA particles obtained by measuring 200 random particles, according to an embodiment of the present invention. [Figure 13B] FIG. 1 shows the size distribution of NCA particles obtained by measuring 200 random particles, according to an embodiment of the present invention. [Figure 14A] 14A-14C are diagrams demonstrating that individual particles are inserted into emulsion droplets by an embodiment of the present invention. NCA particles were mixed with graphene at a ratio of 200:1, with the volume ratio of A / H set at 5:1. Individual particles were then tracked in solution by optical microscopy during drying. [Figure 14B] Comparison images of individual particles before (left) and after (right) drying. [Figure 14C] Schematic of the drying process: As the hexane droplets collapse, the graphene on the droplet surface conformally coats the NCA particles inside. [Figure 15]Figure 1 shows NCA particles coated with 0.5 wt% graphene as observed by scanning electron microscopy (SEM) at various magnifications according to an embodiment of the present invention. The particles were coated with a volume ratio of A / H of 5:1 and dried using fractional distillation. All particles observed were uniformly coated with graphene. [Figure 16] FIG. 1 illustrates a rotary evaporator used in experiments according to an embodiment of the present invention. The bath temperature was set at 50° C. and the rotary beaker speed was set at 100 rpm. [Figure 17] FIG. 13 shows the dispersion behavior after only the hexane has been removed according to an embodiment of the present invention (i.e., the graphene encapsulated NCA powder is now dispersed only in acetonitrile). After repeatedly stirring the mixture for 10 minutes and then letting it sit for 10 minutes, the graphene flakes remain attached to the surface of the NCA powder. [Figure 18] 1 shows the thermogravimetric analysis (TG) and differential thermal analysis (DTA) in an O2 atmosphere at a heating rate of 5° C. / min. The DTA shows that the mixture of EC, graphene, and NCA particles undergoes a heat absorption reaction around 250° C. The TG also shows a mass change of about 1%, which is consistent with the original amount of EC. [Figure 19] Figure 1 shows a transmission electron microscope (TEM) image of graphene-coated NCA particles after pyrolysis of EC according to an embodiment of the present invention, where most of the surface was covered with one to two multi-layer graphene flakes. [Figure 20] FIG. 1 shows a scanning electron microscope (SEM) image of graphene-coated NCA particles after pyrolysis of EC, according to an embodiment of the present invention. [Figure 21] 4F shows energy dispersive spectroscopy (EDS) results corresponding to FIG. 4F in accordance with an embodiment of the present invention. [Figure 22] 1 shows EDS results for pristine NCA particles according to an embodiment of the invention, showing a substantial absence of carbon signal. [Diagram 23]1 shows an electrode with 0.5 wt % carbon black populated with NCA particles according to an embodiment of the invention, suggesting that many of the NCA particles are not well connected electrically. [Figure 24A] 24A-24C are graphs showing galvanostatic profiles as a function of rate. An electrode with 0.5 wt % graphene was charged to 4.3 V at a rate of 1 C and discharged to 2.8 V at rates of 1 C, 2 C, 5 C, and 10 C. [Figure 24B] An electrode containing 5% by weight of carbon black was charged to 4.3 V at a rate of 1 C and discharged to 2.8 V at rates of 1 C, 2 C, 5 C, and 10 C. [Figure 24C] An electrode containing 0.5 wt % carbon black according to an embodiment of the invention was charged to 4.3 V at a rate of 1 C and discharged to 2.8 V at rates of 1 C, 2 C, 5 C, and 10 C. [Figure 25A] 1 is a graph showing the rate capability of 0.5 wt. % graphene, 0.5 wt. % carbon black, and 5 wt. % carbon black electrodes at 6 mg cm-2 areal loading (volumetric capacity) in accordance with an embodiment of the invention. [Figure 25B] 1 is a graph showing the rate capability of 0.5 wt. % graphene, 0.5 wt. % carbon black, and 5 wt. % carbon black electrodes at 6 mg cm-2 areal loading (specific capacitance) in accordance with an embodiment of the invention. [Figure 26] 1 is a graph showing the coulombic efficiency for 1C charge / discharge cycling according to an embodiment of the present invention. The 0.5 wt% carbon black electrode showed significantly lower coulombic efficiency after 50 cycles. On the other hand, the 0.5 wt% graphene and 5 wt% carbon black electrode showed a coulombic efficiency of about 99.7% after more than 100 cycles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0053] The present invention will now be described more fully hereinafter with reference to the accompanying drawings, in which exemplary embodiments of the invention are shown. The present invention may, however, be embodied in many different forms and should not be construed as limited to the embodiments set forth herein. Rather, these embodiments are provided so that this disclosure will be thorough and complete, and will fully convey the scope of the invention to those skilled in the art. Like reference numerals refer to like elements throughout.

[0054] The terms used herein generally have their ordinary meaning in the art, in the context of the present invention and in the specific context in which each term is used. Certain terms used to describe the present invention are discussed below or elsewhere in this specification to provide further guidance to the practitioner regarding the description of the present invention. For convenience, certain terms may be highlighted, such as by using italics and / or quotation marks. The use of highlighting does not affect the scope and meaning of a term, which is the same in the same context whether it is highlighted or not. It is understood that the same thing can be said in multiple ways. As a result, alternative phrases and synonyms may be used for any one or more of the terms discussed herein, and there is no special significance to whether a term is detailed or discussed in this specification. Synonyms for certain terms are provided. The detailed description of one or more synonyms does not exclude the use of other synonyms. The use of examples anywhere in this specification, including examples of any term discussed in this specification, is merely exemplary and does not limit the scope and meaning of the invention or the term exemplified in any way. Likewise, the present invention is not limited to the various embodiments presented herein.

[0055] As used in the description herein, and throughout the claims that follow, the meanings of "a," "an," and "the" should be understood to include plural references unless the context clearly dictates otherwise. Also, when an element is referred to as being "on" another element, it should be understood that it may be directly on the other element, or that intervening elements may be present between them. In contrast, when an element is referred to as being "directly on" another element, there are no intervening elements present. As used herein, the term "and / or" includes any and all combinations of one or more of the associated listed items.

[0056] In this specification, terms such as first, second, third, etc. may be used to describe various elements, components, regions, layers, and / or portions, but it should be understood that these elements, components, regions, layers, and / or portions should not be limited by these terms. These terms are used only to distinguish one element, component, region, layer, or portion from another element, component, region, layer, or portion. Thus, a first element, component, region, layer, or portion discussed below could be referred to as a second element, component, region, layer, or portion without departing from the teachings of the present invention.

[0057] Additionally, relative terms such as "lower" or "bottom" and "upper" or "top" may be used herein to describe the relationship of one element to another element as depicted in the figures. It should be understood that the relative terms are intended to encompass different orientations of the device in addition to the orientation depicted in the figures. For example, if a device in one of the figures is flipped over, an element described as being on the "lower" side of the other element would be oriented on the "upper" side of the other element. Thus, the exemplary term "lower" may encompass both an orientation of "lower" and "upper," depending on the particular orientation of the figure. Similarly, if a device in one of the figures is flipped over, an element described as being "below" or "below" the other element would be oriented "above" the other element. Thus, the exemplary term "lower" or "bottom" may encompass both an orientation of upper and lower.

[0058] Furthermore, terms such as "comprises" and / or "comprising", or "includes" and / or "including", or "has" and / or "having", or "carry" and / or "carrying", or "contain" and / or "containing", or "involve" and / or "involving", should be understood to be open-ended, i.e., to mean including, but not limited to, When used in this disclosure, they specify the presence of stated features, regions, integers, steps, operations, elements, and / or components, but do not preclude the presence or addition of one or more other features, regions, integers, steps, operations, elements, components, and / or groups thereof.

[0059] Unless otherwise defined, all terms (including scientific and technical terms) used herein have the same meaning as commonly understood by those skilled in the art to which the present invention belongs. Furthermore, terms such as those defined in commonly used dictionaries should be interpreted as having a meaning consistent with their meaning in the context of the relevant art and this disclosure, and are not to be interpreted in an ideal or overly formal sense unless expressly defined in this specification.

[0060] As used in this disclosure, "around," "about," "approximately," or "substantially" are generally intended to mean within 20 percent, preferably within 10 percent, and more preferably within 5 percent of a given value or range. Numerical values ​​given herein are approximate, meaning that the terms "around," "about," "approximately," or "substantially" can be estimated unless expressly stated.

[0061] As used in this disclosure, the phrase "at least one of A, B, and C" should be construed to mean the logical (A or B or C) using a non-exclusive logical OR. As used herein, the term "and / or" includes any and all combinations of one or more of the associated listed items.

[0062] Hereinafter, the embodiments of the present invention will be described in detail with reference to the accompanying drawings. The following description is merely exemplary in nature and is not intended to limit the present invention, its application, or use in any way. The broad teachings of the present invention can be implemented in various forms. Therefore, although the present invention includes specific examples, the true scope of the present invention should not be so limited. Because other variations will become apparent by studying the drawings, the specification, and the claims. For the purpose of clarity, the same reference numbers are used in the drawings to identify similar elements. It should be understood that one or more steps in the method can be performed in different orders (or simultaneously) without changing the principles of the present invention.

[0063] LiNi 0.8 Co 0.15 Al 0.05 O 2 (NCA) and LiNi 0.8 Co 0.1 Mn 0.1 O 2 Ni-rich layered cathodes such as (NCM) have a capacity of about 200 mAh g -1 LiCoO is one of the most successful classes of lithium-ion battery (LIB) cathode materials due to their reversible gravimetric capacity approaching 1000 times that of conventional LiCoO. This class of cathode materials is becoming more popular due to the increasing range of Ni-based redox chemistries. 2 Capacity limit (140mAh g -1) are typically synthesized as primary nanoparticles, which are then agglomerated into microscale secondary particles. This scheme allows for a large active surface area of ​​the primary nanoparticles and a high packing density of the secondary microparticles, so that the volumetric capacity of Ni-rich cathode materials is predicted to reach about 690 mAh per cc. Rock salt and pure LiNiO 2 Further high capacity cathode materials such as the above-mentioned phase are under development, but their cycling stability is not yet sufficient for most practical applications.

[0064] Although Ni-rich layered cathodes have inherently high capacity, the actual volumetric and specific capacity of the entire electrode also depends on the inactive components. In addition to the active material, conventional LIB electrodes contain conductive additives (most commonly carbon black) and polymer binders (typically polyvinylidene fluoride (PVF), polyvinylidene difluoride (PVDF), or carboxymethyl cellulose (CMC)). Furthermore, the intraelectrode pores that provide the lithium ion pathways can occupy more than 25% of the total electrode volume. The conductive additives and electrode porosity play a central role in determining the kinetics of the battery, as they are involved in the transport of electrons and lithium ions, respectively. The polymer binder is also important for stable electrochemical cycling by promoting and maintaining the adhesion of the carbon conductive additive to the active material. Despite their importance, the goal is to minimize these inactive components, as they impair the overall specific capacity of the electrode. Even more concerning is that the inclusion of inert components significantly reduces the volumetric capacity of the electrode due to the low tap density of conventional carbon additives, as shown diagrammatically in Figure 1 A. For example, the overall pressed density of a standard NCA electrode is approximately 3.6 g cc for a 5 wt% carbon black loading (Table 1). -1 From about 2.9g cc -1 which is at the low end of typical conductive additive loadings reported in the literature to date.

[0065] [Table 1]

[0066] An attractive solution to maximize both the specific and volumetric capacitance of LIB electrodes is to minimize the conductive additive loading. This strategy also has the potential to limit binder loading since the total surface area of ​​the electrode components is reduced. However, it has proven difficult to construct LIBs that yield acceptable electrochemical performance at low conductive additive loadings. To illustrate this challenge, Figure 1B shows a close-up schematic of an electrode with minimal carbon black loading. Carbon black particles have a spherical shape with a typical diameter of about 100 nm, so it is difficult to form a percolating electrical network unless a significant amount of carbon black is blended into the electrode to fill the interstitial spaces. Furthermore, point contacts between carbon black and active material particles result in current crowding that causes ohmic drop and overpotential problems. These issues are compounded by the need for industrially relevant active material surface loadings (~10 mg cm), which require large electrode thicknesses. -2 ) tends to worsen.

[0067] These limitations of particle-based conductive additives can potentially be overcome by an electrode design in which each active material particle is coated with a thin conductive coating according to the present invention, as shown in FIG. 1C. In addition to achieving extremely high active material packing density, this design minimizes the internal structural complexity of electrodes incorporating carbon black particles, thus reducing lithium-ion tortuosity. Graphene is a good candidate for coating active material particles due to its high electrical conductivity, atomically thin nature, and compatibility with the electrochemical environment inside LIBs. Assuming that graphene forms conformal contacts on the active material particle surface, as shown in FIG. 1D, electron transport is uniformly distributed, thus minimizing current crowding and electrode polarization. Although mass production of high-quality graphene has already been developed, the lack of a scalable coating method that results in conformally coated LIB active material particles has hindered the full realization of this strategy. In particular, previously attempted schemes for mixing graphene with LIB active material particles result in poor electrical conductivity (hence the need to add carbon black conductive additives) and wrinkling of the graphene, both of which lead to low tap density and compromise volumetric capacity.

[0068] One of the objectives of this invention is to disclose conformal ultrathin conductive graphene coatings on LIB active material particles using a scalable Pickering emulsion method that overcomes the above limitations. This approach utilizes high-quality solution-exfoliated graphene with exceptional electrical conductivity, thus enabling industrially relevant active material surface loadings (~11 mg cm). -2Only 0.5 wt. % graphene is required to achieve high electrochemical performance in thick electrodes with 100% active material loading. Due to the exceptionally low inactive material loading, the resulting NCA electrodes achieve specific and volumetric capacities within about 98% of the theoretical limits for NCA materials. Efficient electron and lithium ion transport in these electrodes also results in superlative rate capabilities, while the conformal graphene coating mitigates electrochemical degradation mechanisms, resulting in improved cycle life. Although demonstrated in the disclosure for NCA cathodes, this Pickering emulsion coating scheme is likely generalizable to other active material particles, thus providing a route to theoretical specific and volumetric capacities in practical LIB electrodes.

[0069] According to one aspect of the invention, a method for producing a composite material using a scalable Pickering emulsion approach includes forming an emulsion mixture of active material particles and graphene emulsion droplets containing immiscible first and second solvents and a graphene solid-state emulsifier, the first and second solvents being adapted such that the first solvent is an exterior solvent and the second solvent is present inside the graphene emulsion droplets, and the active material particles are present inside the emulsion droplets.

[0070] In some embodiments, the boiling point of the second solvent is lower than the boiling point of the first solvent. For example, the first solvent includes, but is not limited to, acetonitrile, heptane, water, or acetic acid, and the second solvent includes, but is not limited to, pentane, cyclohexane, acetonitrile, benzene, hexane, or chloroform. It should be understood that the present invention can be practiced using any combination of the first solvent and the second solvent, as long as two immiscible solvents are provided and the second solvent has a lower boiling point than the first solvent. Table 2 lists some examples of combinations of the first solvent and the second solvent that can be used to practice the present invention.

[0071] [Table 2]

[0072] The volume ratio of the first solvent to the second solvent can range from about 5:4 to about 5:1.

[0073] In some embodiments, the average size of the graphene emulsion droplets is varied by varying the volume ratio of the first solvent to the second solvent and the concentration of the graphene in the base solution, in some embodiments, the average size of the graphene emulsion droplets shrinks as the content of the second solvent decreases and is less than about 5 μm at a volume ratio of the first solvent to the second solvent of 5:1.

[0074] In some embodiments, the graphene comprises solution exfoliated graphene. The weight ratio of the graphene to active material particles can range from about 1:400 to about 1:100, preferably about 1:200.

[0075] In one embodiment, the step of forming an emulsion mixture includes dispersing the graphene in a first solvent to form a base solution, mixing a second solvent with the base solution to form graphene emulsion droplets by sonication, and inserting active material particles into the graphene emulsion droplets by agitation.

[0076] In another embodiment, the step of forming an emulsion mixture includes dispersing the graphene in a first solvent to form a base solution, dispersing active material particles in the base solution to form a first mixture, adding a second solvent to the first mixture to form a second mixture, and sonicating the second mixture to intercalate the active material particles into the graphene emulsion droplets.

[0077] The method further includes a drying process of the emulsion mixture, which needs to be carefully controlled to achieve a conformal graphene coating on the active material particles, which is carried out by subsequently evaporating the second solvent and the first solvent by fractional distillation to form a composite material in which each surface of the active material particles is conformally coated with said graphene.

[0078] For example, in one embodiment, the first solvent is acetonitrile, which has a boiling point of 82° C., and the second solvent is hexane, which has a boiling point of 68° C. Fractional distillation is carried out in a rotary evaporator with the bath temperature set at about 50° C. and the pressure set at about 0.6 atm for a first period of time to completely and selectively remove the hexane, thereby resulting in controlled collapse of the emulsion droplets and conformal graphene coating on the active material particles, and then the pressure is reduced to less than 0.2 atm for a second period of time to completely remove the acetonitrile, thereby resulting in conformal graphene-coated active material particles.

[0079] In some embodiments, the graphene emulsion droplets may also contain ethyl cellulose (EC) as an additive to enhance the dispersibility and emulsifier properties of the graphene. The weight ratio of the graphene to the EC may range from about 1:0 to about 1:3, preferably about 1:2. In one embodiment, thermal annealing at a temperature in the range of about 150 to 350°C, preferably about 250°C, is performed in an oxidizing environment to decompose most of the EC, and the remaining amorphous carbon residue is converted to a high sp ion ... 2 Has carbon content.

[0080] According to another aspect of the invention, a composite material includes graphene and active material particles, each surface of the active material particles being conformally coated with said graphene, in some embodiments, each surface of the active material particles being conformally coated with said graphene by a Pickering emulsion process, as discussed above.

[0081] In some embodiments, the composite material comprises sp 2 , which facilitates electron transport between the graphene flakes. 2 It may have amorphous carbon having carbon content. Amorphous carbon is an annealing product of EC.

[0082] In some embodiments, the graphene comprises solution exfoliated graphene, In some embodiments, the weight ratio of the graphene to active material particles is in the range of about 1:400 to about 1:100, preferably about 1:200.

[0083] In some embodiments, the active material includes lithium cobalt oxide, lithium iron phosphate, lithium manganese oxide, lithium nickel manganese cobalt oxide, lithium nickel cobalt aluminum oxide, or combinations thereof.

[0084] In some embodiments, the active material includes nickel-rich lithium oxide.

[0085] In some embodiments, the active material is LiNi 0.8 Co 0.15 Al 0.05 O 2 (NCA), LiNiO 2 (LNO), LiMn 1.5 Ni 0.5 O 4 (LMNO), LiNi x Mn y Co z O 2 (NMC, in the formula, x+y+z=1), LiNi 0.8 Co 0.2 O 2 (LNCO), or Li w Ni x Mn y Co z O 2 (lithium-rich NMC, where w>1, x+y+z=1). The active material may be doped with elements including Al, B, Zr, Nb, Fe, Cr, Cu, Mo, W, and / or V.

[0086] An aspect of the present invention also relates to an electrode and an electrochemical device, such as a lithium-ion battery (LIB), that includes the electrode. The electrode is formed from a composite material that includes graphene and active material particles. Each surface of the active material particles is conformally coated with the graphene, as discussed above.

[0087] To achieve the high energy densities required by emerging technologies, LIB electrodes must approach the volumetric and specific capacity limits of their electrochemically active components, which requires minimizing the inactive components of the electrode. However, reducing the proportion of inactive conductive additives limits charge transport in the battery electrode, thereby compromising electrochemical performance. These shortcomings are overcome by the electrode design of the present invention, which does not require the inclusion of inactive conductive additives such as carbon black, and achieves efficient electron and lithium ion transport kinetics at exceptionally low conductive additive levels and industrially relevant active material surface loadings. For example, in some embodiments, electrodes with as little as 0.5% by weight of graphene can achieve approximately 10 mg cm -2 The present invention achieves greater than 100% active material surface loading, as well as volumetric and specific capacitances that are at least about 98% of the theoretical limits of the active materials.

[0088] Furthermore, the conformal graphene coverage reduces degradation at the cathode surface, thus providing improved electrochemical cycle life. For example, in some embodiments, an electrode having as little as 0.5% by weight of graphene retains about 91.5% of its initial volumetric capacity over 100 cycles and maintains a coulombic efficiency of about 99.7%. Furthermore, an electrode having as little as 0.5% by weight of graphene retains about 70% of its initial volumetric capacity over 250 cycles.

[0089] These electrode morphologies also promote rapid lithium ion transport kinetics, thereby providing high rate capability. Overall, this electrode design simultaneously approaches the theoretical volumetric and specific capacity limits without tradeoffs in cycle life, rate capability, or active material surface loading.

[0090] In accordance with the present invention, the Pickering emulsion method provides highly conformal graphene coatings that allow for an order of magnitude reduction in inactive component levels, thereby resulting in unprecedented battery performance metrics. Importantly, the Pickering emulsion method is also highly manufacturable due to its scalability, high throughput, and recyclability.

[0091] Moreover, the Pickering emulsion coating method simultaneously overcomes the limited scalability and quality of previous graphene coatings. In particular, existing strategies to coat active materials for Li-ion batteries have been carried out using functionalized graphene, such as graphene oxide or reduced graphene oxide, rather than utilizing high-quality pristine graphene. Furthermore, these existing strategies employ harsh chemicals that may further damage the graphene coating and / or the underlying electrode material. Furthermore, due to the conformal nature of the coating, we achieve an order of magnitude reduction in inactive components in Li-ion battery electrodes, which results in unprecedented battery performance metrics, including high specific and volumetric capacity, rate capability, cycle life, and coulombic efficiency.

[0092] Applications of the present invention include, but are not limited to, Li-ion batteries, graphene coatings, cathode materials, conductive additives, and the like.

[0093] Among other advantages, the present invention has at least the following advantages over existing technology:

[0094] Existing scalable coating methods are only applicable to graphene oxide or low quality graphene, whereas the Pickering emulsion method of the present invention can be applied to pure graphene as well as functionalized graphene without further chemical / physical damage.

[0095] Existing coating methods using high quality graphene are only able to coat materials on a small scale, however the Pickering emulsion method of the present invention is able to coat materials in parallel on a large scale.

[0096] The Pickering emulsion method of the present invention results in highly uniform graphene coating compared to other existing coating methods.

[0097] The Pickering emulsion process of the present invention is scalable, high throughput, and recyclable.

[0098] The conformal graphene coating of the present invention allows for an order of magnitude reduction in the percentage of inactive material in a battery electrode.

[0099] Electrodes using the graphene coatings of the present invention provide excellent specific and volumetric capacity, rate capability, cycle life, and coulombic efficiency for Li-ion batteries.

[0100] These and other aspects of the present invention are further described below. Without intending to limit the scope of the present invention, exemplary devices, apparatus, methods, and their related results described in the embodiments of the present invention are set forth below. Please note that titles or subtitles may be used in the examples for the convenience of the reader, but this does not limit the scope of the present invention in any way. Furthermore, although certain theories are proposed and disclosed herein, these theories, whether correct or incorrect, do not limit the scope of the present invention in any way, so long as the present invention is practiced according to the present invention regardless of any particular theory or operation scheme. EXAMPLES

[0101] Simultaneously approaching the volumetric and specific capacity limits of lithium battery cathodes with conformal Pickering emulsion graphene coatings Among other things, this illustrative example discloses conformal ultrathin conductive graphene coatings on LIB active material particles using a scalable Pickering emulsion method. This approach uses high-quality solution-exfoliated graphene with exceptional electrical conductivity, enabling industrially relevant active material surface loadings (~11 mg cm). -2 Only 0.5 wt. % graphene is required to achieve high electrochemical performance in thick electrodes with 100% active material loading. Due to the exceptionally low inactive material loading, the resulting NCA electrodes achieve specific and volumetric capacities that are within about 98% of the theoretical limits for NCA materials. Efficient electron and lithium ion transport in these electrodes also results in superlative rate capabilities, while the conformal graphene coverage mitigates electrochemical degradation mechanisms, resulting in improved cycle life. Although demonstrated here for NCA cathodes, this Pickering emulsion coverage scheme is likely generalizable to other active material particles, thus providing a route to theoretical specific and volumetric capacities in practical LIB electrodes.

[0102] Preparation of graphene Graphite exfoliation was carried out by mixing 6,000 g of flake graphite and 200 g of 4cP ethylcellulose (both from Sigma Aldrich) in a reservoir tank containing 5 L of 200 proof ethanol (Decon Labs, Fisher Scientific Co). This mixture was continuously circulated by a 200 L in-line shear mixer (Silverson Machines). After 23 hours, the resulting mixture was centrifuged at 6,500 rpm for 0.5 hours in an Avanti J-26 XPI centrifuge using a JLA 8.1000 rotor (both from Beckman Coulter Inc.). The ethanol-based supernatant containing polydispersed graphene with EC was then collected and flocculated by adding NaCl brine. The precipitated solids of graphene, EC, and salt were collected, combined in a 1 L Buchner funnel, and washed repeatedly with deionized water. The solid material was then transferred to a Pyrex container and dried at ambient conditions using a 150 W infrared lamp to completely dehydrate the sample. The dried graphene and EC mixture was dispersed in acetonitrile (Sigma Aldrich) using horn sonication at 30-40% amplitude for 1 h.

[0103] Conformal graphene coating via Pickering emulsion processing Pickering emulsions are obtained from two immiscible solvents, where the interface of the emulsion droplets is stabilized by a solid-state emulsifier. As a first step to achieve conformal graphene coverage, Pickering emulsions were formed using acetonitrile and hexane as immiscible solvents and graphene (Gr) as a solid-state emulsifier, as shown diagrammatically in Figure 2A. The conditions of the Pickering emulsion were selected such that a high boiling point solvent (i.e., acetonitrile: boiling point = 82 °C) was present as the external solvent and a low boiling point solvent (i.e., hexane: boiling point = 68 °C) was present inside the emulsion droplets. In addition, ethyl cellulose (EC) was used as an additive to enhance the dispersibility and emulsifier properties of graphene. NCA particles were present inside the emulsion droplets because they preferentially dispersed in hexane compared to acetonitrile. The selection of solvents for the Pickering emulsions was based on their compatibility with the NCAs, in addition to their low and different boiling points, which facilitate the formation of uniform graphene coatings, as discussed further below (Figures 7A-8).

[0104] The detailed procedure for forming Pickering emulsions begins by dispersing graphene in acetonitrile to form a base solution. With regard to the dispersibility of graphene in acetonitrile, it is worth noting that there is still debate as to whether the surface chemistry of graphene is hydrophobic or hydrophilic, but graphene itself is generally observed to be difficult to disperse in many solvents, including ethanol, water, and acetonitrile. However, previous studies have demonstrated that stable graphene dispersions can be prepared in ethanol by using EC as a stabilizer. Similarly, the inventors have found that graphene can be effectively dispersed in acetonitrile using EC. Figure 2B shows the degree of dispersion of graphene in acetonitrile as a function of the relative mass ratio of graphene to EC. The graphene itself was obtained from liquid-phase exfoliation using a procedure previously disclosed. As shown by atomic force microscopy (AFM) in Figure 2C, the multilayer graphene flakes have an average lateral size of about 160 nm and an average thickness of about 3 nm (AFM histogram depicted in Figure 9B). Graphene was dissolved in acetonitrile at about 0.275 mg mL -1 or a 1:1 EC mass ratio (in this case, the EC concentration is also about 0.275 mg mL -1 When dispersed alone in EC (i.e., 1:2 graphene:EC ratio), aggregation of graphene occurred within about 24 h after horn sonication, as shown in the lower panel of Figure 2B. On the other hand, when the relative amount of EC was increased (i.e., 1:2 graphene:EC ratio), the resulting graphene dispersion was stable without aggregation for more than a week.

[0105] The optimal 1:2 Gr / EC dispersion in acetonitrile formed a Pickering emulsion when the immiscible hexane solvent was added. Specifically, Figure 2D shows a series of 5 mL Gr / EC in acetonitrile dispersions in decreasing volumes of hexane (4 mL to 1 mL hexane from left to right) after vortex mixing for 1 min. The concentrations of Gr and EC in acetonitrile were approximately 0.275 mg mL, respectively. -1 and approximately 0.55 mg mL-1 All acetonitrile / hexane (A / H) mixtures showed graphene separation to the top layer in addition to the formation of floating emulsion droplets that were stable in size for a week. The density of hexane (approximately 0.65 g mL -1 ) is acetonitrile (approximately 0.79 g mL -1 ), one can infer that the internal solvent of the suspended droplets is hexane rather than acetonitrile. Consistent with this interpretation, the average size of the emulsion droplets decreased with decreasing hexane content, as shown in FIG. 2E. Emulsion droplets with diameters greater than about 100 μm were observed at a 5:4 ratio of acetonitrile to hexane, while the diameter of the emulsion droplets decreased to less than about 5 μm at a 5:1 ratio of acetonitrile to hexane, as shown in FIG. 10. No further reduction in emulsion droplet size was observed at even lower hexane contents, as shown in FIG. 11. Furthermore, the concentration of graphene also altered the average size of the emulsion droplets (FIG. 12), an observation consistent with other Pickering emulsions.

[0106] After preparing the Pickering emulsion, the NCA particles were inserted into the emulsion droplets. Considering the actual surface area of ​​graphene obtained by the solution exfoliation process (Figures 9A-9B) and the average NCA particle size (Figures 13A-13B), the ideal mass ratio of graphene to NCA was determined to be 1:200. Therefore, approximately 550 mg of NCA powder was added to approximately 10 mL of graphene / acetonitrile solution (approximately 0.275 mg mL -1), and A / H solutions were prepared by bath sonication at ratios of 5:3, 5:2, and 5:1 (from left to right in FIG. 2F). Initially, the emulsion mixtures with NCA were uniformly distributed after 10 min of bath sonication. However, when the emulsion mixtures were then shaken or vortexed, graphene emulsion droplets quickly formed and settled with the NCA powder at all A / H ratios, as shown in FIG. 2F. In contrast, mixtures without hexane or NCA powder did not exhibit this behavior. The settling of the emulsion droplets suggests the intercalation of relatively dense NCA particles, which is confirmed by optical microscopy shown in the lower panel of FIG. 2F and in FIG. 2G. Once the NCA particles were intercalated, the emulsions remained stable for more than a week.

[0107] The right panel of Figure 2G shows the insertion of NCA particles into an emulsion with an A / H ratio of 5:1, where most droplets are less than 5 μm in size. In this case, the emulsion droplets encapsulate individual NCA particles (blue arrow 10) or a relatively small number of NCA particles (red arrow 20). By following the droplet / particle complexes during drying, a clear reduction in droplet size is observed, as shown in Figures 14A-14C, and finally particles are obtained that are conformally coated with graphene, as confirmed by scanning electron microscopy (Figure 15). This conformal encapsulation is possible due to two factors. First, the stable average size of the droplets at an A / H ratio of 5:1 is less than 5 μm, which corresponds to the size of an individual NCA particle. Second, the NCA particles and the emulsion graphene shells interact favorably, which allows efficient formation of Pickering emulsion droplets around each NCA particle. In particular, when NCA particles were present, Pickering emulsion droplets formed immediately upon stirring, whereas the mixture without NCA particles formed emulsion droplets much more slowly.

[0108] The drying process needs to be carefully controlled to achieve conformal graphene coverage on the NCA particles. For example, drying the optimized Pickering emulsion with NCA particles without precise control at standard temperature and pressure (STP) leads to premature rupture of the droplets, which results in non-uniform graphene coverage on the NCA particle surface, as shown diagrammatically on the left side of FIG. 3A. The optical microscope image in FIG. 3B shows the result of this uncontrolled STP drying process, with residual graphene flakes spreading around the NCA particles after premature rupture of the emulsion droplets. On the other hand, conformal graphene coverage on the NCA particles is achieved by selective evaporation of the inner hexane solution by fractional distillation, as shown diagrammatically on the right side of FIG. 3A. This controlled fractional distillation is achieved using a rotary evaporator with a bath temperature set at about 50° C., as shown in FIG. 16. After about 20 minutes at a pressure of about 0.6 atm, the hexane is completely and selectively removed, as shown in FIG. 3D, resulting in controlled collapse of the emulsion droplets and conformal graphene coating on the NCA particles. After removal of the hexane, the resulting dispersion containing graphene-encapsulated NCA powder in acetonitrile exhibits exceptional stability. Notably, as shown in FIG. 17, the NCA powder does not separate from the graphene coating upon stirring. Further reduction of the pressure in the rotary evaporator to below 0.2 atm results in complete removal of the acetonitrile, as shown in FIG. 3D, resulting in fully graphene-coated NCA particles. As shown in FIG. 3E-H, SEM characterization confirms the effectiveness of fractional distillation in achieving conformal graphene coating on the NCA particles.

[0109] Another advantage of the Pickering emulsion graphene coating scheme is its scalability. Figure 4A shows a 10 gram scale process of NCA powder, which starts with dispersing the NCA powder in about 180 mL of graphene dispersed in acetonitrile, with a graphene to NCA mass ratio of 1:200. Before adding hexane (Figure 4A, left), the graphene is well dispersed in acetonitrile, but the NCA particles settle and separate from the mixture. After adding about 36 mL of hexane and bath sonicating for about 10 min, Pickering emulsion droplets form and settle (Figure 4A, right), similar to Figure 2F. Subsequent fractional distillation yields NCA powder conformally coated with graphene. Because the hexane and acetonitrile solvents are extracted separately by fractional distillation, these solvents can be easily reused for subsequent Pickering emulsions. Overall, the entire coating process takes less than 2 hours until the graphene-coated NCA powder is completely dried. Due to its scalability, high throughput, and recyclability, the Pickering emulsion process can be directly applied to large-scale manufacturing.

[0110] After fractional distillation, the conformal coating on the NCA powder contains graphene and EC. Although the presence of EC may be tolerable or even desirable in some applications, EC must be removed in LIBs because it interferes with the transport of lithium ions and electrons. EC is pyrolyzed in an oxidizing environment at a mild temperature of about 250° C., which is an annealing condition compatible with graphene and active materials in LIBs. Indeed, differential thermal analysis (DTA) and thermogravimetric analysis (TGA) show that OC is a 0.01% cation, as shown in FIG. 18. 2We show that residual EC can be removed after thermal annealing at about 250 °C in ambient air. Further evidence for EC removal is provided by Raman spectroscopy, as shown in Figure 4B, where a significant decrease in the D band is observed after annealing, which is consistent with previous studies of EC pyrolysis in the presence of graphene. Overall, thermal annealing removes most of the EC, and the remaining amorphous carbon residue is converted to high sp ions that facilitate electron transport between graphene flakes. 2 The carbon content is consistent with that of the pristine NCA particles (Figure 2). Transmission electron microscopy (TEM) and SEM, shown in Figures 4C-4E and 19, confirm that the final coating is highly conformal and contains approximately 10 nm of well-defined graphitic carbon. Furthermore, energy dispersive spectroscopy (EDS) elemental mapping, shown in Figures 4F and 21, confirms the uniformity of the carbon coating, while the pristine NCA particles show virtually no carbon signal (Figure 22).

[0111] Electrode fabrication NCA powder was obtained from BASF TODA (HED NCA-1050, lot 1270203). The slurry for the electrodes was blended with active material (NCA or graphene coated NCA), carbon black (MTI Corporation, EQ-Lib-SuperP), and PVDF binder (Corporation, EQ-Lib-PVDF) together with N-methyl-2-pyrrolidone (NMP) for 15 minutes using a planetary centrifugal mixer. The mixed slurry had a density of approximately 11 mg cm. -2 The electrodes were cast on aluminum foil with a surface loading of 1.0 M LiPF in 1:1 volume ratio of ethylene carbonate / dimethyl carbonate for rate capability testing. The electrodes were dried in an oven at 120°C for 20 min and compressed by a roller press (MTI, MSK-HRP-MR100DC). CR2032 coin cells were assembled with lithium metal (MTI Corporation, reference electrode), glass fiber (Whatman, separator), and 1.0 M LiPF in 1:1 volume ratio of ethylene carbonate / dimethyl carbonate for rate capability testing. 6(Sigma Aldrich, EC / DMC, electrolyte) or 1.2 M LiPF in ethylene carbonate / ethyl methyl carbonate in a volume ratio of 3:7 with 2 wt. % vinylene carbonate for cycle retention testing. 6 (Sigma Aldrich, EC / EMC, electrolyte) was used for assembly.

[0112] Electrochemical characterization Li / Li + Electrochemical characterization was performed using an Arbin battery cycler within a voltage range of approximately 2.8 to 4.3 V vs. 1 C. As used herein, 1 C of NCA corresponds to 180 mA g -1 Electrochemical impedance spectroscopy was performed using a Biologic VSP potentiostat. The units used in this disclosure were calculated as follows: (1) Surface filling amount (mg cm -2 ) = (total electrode mass (mg) - Al foil mass (mg)) × active material ratio / electrode area (cm 2 ); (2) Compressed density (packing density, mg cc -1 )=Active loading density (mg cm -2 ) / Thickness(cm); (3) Total electrode specific capacity (mAh g -1 ) = Capacity (mAh) / Total electrode mass (g); and (4) Volumetric capacity (mAh cc -1 ) = Capacity (mAh) / Active substance amount (mg) × Compressed density (mg cc -1 ).

[0113] A LIB cathode with unprecedentedly low conductive additive loading was fabricated using graphene-coated NCA powder. In particular, a mixture of graphene-coated NCA and PVDF binder was cast onto an aluminum current collector in a mass ratio of about 99.2:0.8, suggesting that the overall composition of NCA, graphene, and PVDF was about 98.7:0.5:0.8. To demonstrate the suitability of graphene-coated NCA powder for practical LIBs, a mixture of graphene-coated NCA powder with a mass ratio of about 11 mg cm was cast onto an aluminum current collector. -2A high active material surface loading of about 100 μm was used. Two control electrodes were prepared with different ratios: one with the same carbon additive ratio (i.e., about 98.7:0.5:0.8 ratio of NCA, carbon black, and PVDF) and one with an order of magnitude higher amount of carbon black (i.e., about 90:5:5 ratio of NCA, carbon black, and PVDF). The prepared electrodes were compressed using a commercial rolling machine until cracks were just visible in the film. The SEM images shown in FIG. 5A show that the thicknesses of the 0.5 wt. % graphene, 0.5 wt. % carbon black, and 5 wt. % electrodes are about 30 μm, about 30 μm, and about 37 μm, respectively. The compressed electrode density was about 3.6 mg cc for the 0.5 wt. % graphene and 0.5 wt. % carbon black electrodes. -1 and when carbon black is 5 mass%, it is 2.9 mg cc -1 (Table 2). 3.6 mg cc -1 The compressed electrode density of the NCA material is the highest reported to date (approximately 3.3 mg cc -1 ) which can be attributed to the exceptionally low carbon content made possible by the conformal graphene coating.

[0114] Short lithium ion diffusion length and good percolating electron transport pathways are ideal properties for a LIB electrode. Because the 0.5 wt% graphene and 0.5 wt% carbon black electrodes were thinner and contained little or no porous carbon compared to the 5 wt% carbon black electrodes, the tortuosity of lithium ion diffusion is expected to decrease in the lower carbon content electrodes. Furthermore, the conformal graphene coverage is beneficial for forming percolating electron transport pathways because it can provide a seamless electrical network even at multi-particle contacts. Furthermore, the high electrical conductivity of graphene coupled with its conformal coverage morphology is expected to minimize the overall contact resistance to the NCA particles. Top-view SEM images of the electrodes confirmed the expected difference in the amount of carbon particles present, as shown in Figure 5B and Figure 23, with the 0.5 wt% electrode consisting almost exclusively of active NCA particles.

[0115] To investigate the electronic properties of the as-prepared electrodes, the electrical conductivity was measured using the four-probe method, and the results are summarized in Table 3. The electrode with 0.5 wt% graphene had about 80% of the electrical conductivity of the electrode with 5 wt% carbon black, despite having an order of magnitude less carbon, unlike the electrode with 0.5 wt% carbon black, which was more than two times less conductive. The conformal graphene coverage also facilitates the charge transport kinetics at the active electrode surface. Figure 5C shows the Nyquist plot of the lithium metal two-electrode cell after one activation cycle for the formation of the solid electrolyte interface (SEI) layer. The Nyquist plot exhibits two semicircles, which are typical for a layered cathode electrode. The first and second semicircles are the diffusion of lithium ions through the SEI layer (R f ) and charge transfer at the surface (R ct The graphene-coated NCA electrode showed a significant improvement in R compared to other electrodes, as summarized in Table 3. f and R ctThe resistivity and conductivity of the prepared electrodes were measured by the four-probe method. The average conductivity was obtained from five measurements for each electrode. The convoluted impedance (R f ) and charge transfer at the surface (R ct ) were obtained by electrochemical impedance spectroscopy.

[0116] [Table 3]

[0117] The electrochemical properties of the as-prepared electrodes were further evaluated using lithium metal half-cells. Figure 5D shows the galvanostatic profile of the electrode at C / 10 rate in the first cycle. The gravimetric capacity of the electrodes was determined not only from the mass of the active material but also including the mass of the binder and carbon components to focus on the overall electrode capacity. As typically observed for Ni-rich layered oxide cathodes, a large irreversible capacity was observed in the first cycle for all electrodes. The first discharge capacity of the electrode with 0.5 wt% graphene was 191 mAh g -1 while the electrodes with 0.5% and 5% carbon black by weight had 179 mAh g -1 and 185mAh g -1 The gravimetric capacity of the NCA itself is typically about 195 mAh g for the first discharge. -1 Impressively, the 0.5 wt% graphene electrode achieved 98% of this value, even considering all inactive components, while the 0.5 wt% and 5 wt% carbon black electrodes showed lower usable capacity due to limited electron transport and a large proportion of inactive components, respectively. Furthermore, an overshoot at a shoulder of about 3.7 V was observed in the initial charge profile of the 0.5 wt% graphene electrode, as is commonly observed for other coated LIB materials.

[0118] The rate capability of the 0.5 wt% graphene electrodes was superior to the other electrodes in terms of both volumetric capacity and total electrode weight capacity (Figures 5E-5F). The volumetric capacity of the 0.5 wt% graphene electrodes was at least 20% higher than the 5 wt% carbon black electrodes for all current densities tested, as shown in Figure 5E. This improved volumetric capacity results from replacing the bulky carbon black with a conformal graphene coating, thereby significantly increasing the packed electrode density. The 0.5 wt% carbon black electrodes also yielded high packed electrode density, but showed much lower rate capabilities due to their poor electron penetration. The 0.5 wt% graphene electrodes show a similar rate capability advantage as for the total electrode weight capacity. The constant current profiles of all electrodes are shown in Figures 24A-24C. Previous studies have revealed that the electrochemical reaction of relatively high loading electrodes is limited by the diffusion of lithium ions in the electrolyte at high C-rates. As a result, as shown in Figures 25A-25B, the surface loading was approximately 6 mg cm. -2 By scaling down to 0.5 wt % graphene, even higher rate capabilities up to 20 C can be realized for electrodes with 0.5 wt % graphene.

[0119] The 0.5 wt% graphene electrode also had excellent cycle retention, as shown in FIG. 5G. For the 0.5 wt% carbon black electrode, the capacity retention at 1C was significantly compromised within the first 10 cycles. This may be due to the insulating SEI layer on the surface leading to irreversible decomposition of the electronic network. On the other hand, the 5 wt% carbon black and 0.5 wt% graphene electrodes retained 90.5% and 91.5% of their initial volumetric capacity, respectively, over 100 cycles, as shown in FIG. 5G, while also maintaining a coulombic efficiency of about 99.7%, as shown in FIG. 26. However, with 5 wt% carbon black, a sudden mild short circuit profile was consistently observed before 125 cycles, while the 0.5 wt% graphene electrode could still be cycled more than 250 times while maintaining about 70% of its initial capacity. Previous studies have shown that electrodes with high loadings (10 mg cm) were able to be cycled more than 250 times while maintaining about 70% of its initial capacity. -2 (>100 cycles) have been shown to typically retain less than 80% of their initial capacity after 100 cycles. Furthermore, studies based on high loading electrodes rarely report >100 cycles due to the possibility of severe current crowding caused by even small amounts of side reactions accumulating at the electrode. The world-class cycling performance of the 0.5 wt% graphene electrode stems from its simplified electrode structure and the chemical inertness of graphene, which minimizes electrolyte decomposition.

[0120] Figures 6A-6C compare the electrochemical results of this study with the theoretical limits and the best LIB cathodes reported so far in the literature. In particular, the star markers in Figure 6A represent the practically achievable volumetric and specific capacitance limits of LIB electrodes based on the most common cathode material: LiFePO 4 (LFP), LiCoO 2(LCO), NCM, and NCA. These limits correspond to the theoretical specific capacity of the active material that can be realized simply at the electrode level without binders or conductive additives, while the volumetric capacity assumes an ideal crystal density with 25% porosity for lithium ion diffusion, which is the porosity limit experimentally observed in highly compact electrodes. Among the plotted data points, the nickel-rich cathode is the most promising for high specific and volumetric capacity due to the advantages of Ni redox chemistry. However, current electrode engineering strategies have not been able to realize performance close to the theoretical limit of these high capacity cathode materials, as shown by the round markers that show the results of previous studies on NCA and NCM. On the other hand, the electrode with 0.5 wt % graphene reaches about 98% of its volumetric and specific capacity limits.

[0121] The 0.5 wt. % graphene electrode not only pushes the limits of volumetric and specific capacitance, but also achieves unprecedented rate performance. Figures 6B-6C show a comparison of the volumetric and specific rate capabilities, respectively, compared to the best-in-class results to date for Ni-rich cathodes. For the comparison to be credible, the results shown in Figures 6B-6C require at least 7 mg / cm 2 The volumetric capacity of the electrode with 0.5 wt. % graphene (Figure 6B) shows an increase of at least 10% over the entire current density range, reaching 500 mAh cc at a 5 C rate. -1 An exceptionally high volumetric capacity of 1000 μm was achieved. Furthermore, the total electrode specific capacity also delivered excellent performance at all current densities, as shown in Figure 6C. This superlative rate performance again confirms the exceptional electron and lithium ion transport properties offered by the electrode based on the conformal graphene coating.

[0122] conclusion In the illustrative examples / embodiments, a highly conformal graphene coating method based on Pickering emulsion processing is disclosed. This methodology could be used in manufacturing settings due to its high scalability, throughput, and recyclability. The resulting conformal graphene coating allows the amount of carbon conductive additive in LIB electrodes to be substantially reduced without compromising the electron transport pathway. Correspondingly, the polymer binder level can also be reduced, resulting in exceptionally high active material fraction and packing density. The resulting electrodes show unprecedented high practical volumetric and specific capacitances approaching the theoretical capacity limit at high areal loadings. Furthermore, efficient electron and lithium ion transport in these electrodes suggests superlative rate capabilities, while the conformal graphene coating mitigates degradation pathways, thereby resulting in exceptional cycle life. Although shown here to be particularly effective for LIB electrodes, the Pickering emulsion processing scheme could be generalized for coating a variety of particles with graphene and related 2D materials.

[0123] The foregoing description of exemplary embodiments of the invention has been presented for purposes of illustration and description only, and is not intended to be exhaustive or to limit the invention to the precise form disclosed. Many modifications and variations are possible in light of the above teachings.

[0124] The embodiments have been chosen and described to illustrate the principles of the invention and their practical application so that others skilled in the art can utilize the invention and its various embodiments, and so that various modifications are suitable for the particular uses contemplated. Alternative embodiments will become apparent to those skilled in the art to which the invention pertains without departing from the spirit and scope thereof. Thus, the scope of the invention is defined by the appended claims rather than by the foregoing description and the exemplary embodiments described therein.

[0125] Several references, which may include patents, patent applications, and various publications, are cited and discussed in the description of the present invention. Citation and / or discussion of such references is provided merely to clarify the description of the present invention and is not an admission that such references are "prior art" to the inventions described herein. All references cited and discussed herein are incorporated herein by reference in their entirety and to the same extent as if each reference was individually incorporated by reference.

[0126] (References) [1]. Armand, M. & Tarascon, JM Building better batteries. Nature 451, 652-657 (2008). [2]. Lu, L., Han, X., Li, J., Hua, J. & Ouyang, M. A review on the key issues for lithium-ion battery management in electric vehicles. J. Power Sources 226, 272-288 (2013). [3]. Lee, J. et al. Reversible Mn 2+ / Mn 4+ double redox in lithium-excess cathode materials. Nature 556, 185-190 (2018). [4]. Grimaud, A., Hong, WT, Shao-Horn, Y. & Tarascon, JM Anionic redox processes for electrochemical devices. Nat. Mater. 15, 121 (2016). [5]. Arai, H., Okada, S., Sakurai, Y. & Yamaki, J.-i. Reversibility of LiNiO 2cathode. Solid State Ion. 95, 275-282 (1997). [6]. Etacheri, V., Marom, R., Elazari, R., Salitra, G. & Aurbach, D. Challenges in the development of advanced Li-ion batteries: a review. Energy Environ. Sci. 4, 3243-3262 (2011). [7]. Manthiram, A., Knight, J. C., Myung, S.-T., Oh, S.-M. & Sun, Y.-K. Nickel-rich and lithium-rich layered oxide cathodes: Progress and perspectives. Adv. Energy Mater. 6, 1501010 (2016). [8]. Kim, J. et al. Prospect and reality of Ni-rich cathode for commercialization. Adv. Energy Mater. 8, 1702028 (2018). [9]. Lee, J. et al. Unlocking the potential of cation-disordered oxides for rechargeable lithium batteries. Science 343, 519-522 (2014).

[10] . Zheng, H., Tan, L., Liu, G., Song, X. & Battaglia, V. S. Calendering effects on the physical and electrochemical properties of Li[Ni 1 / 3 Mn 1 / 3 Co 1 / 3 ]O 2 cathode. J. Power Sources 208, 52-57 (2012).

[11] . Ebner, M., Geldmacher, F., Marone, F., Stampanoni, M. & Wood, V. X-ray tomography of porous, transition metal oxide based lithium ion battery electrodes. Adv. Energy Mater. 3, 845-850 (2013).

[12] . Jabbour, L., Bongiovanni, R., Chaussy, D., Gerbaldi, C. & Beneventi, D. Cellulose-based Li-ion batteries: a review. Cellulose 20, 1523-1545 (2013).

[13] . Gaines, L. & Cuenca, R. Costs of lithium-ion batteries for vehicles. (Argonne National Lab., IL, US, 2000).

[14] . Dominko, R. et al. The role of carbon black distribution in cathodes for Li ion batteries. J. Power Sources 119-121, 770-773 (2003).

[15] . Li, Y. et al. Effects of particle size, electronic connectivity, and incoherent nanoscale domains on the sequence of lithiation in LiFePO 4 porous electrodes. Adv. Mater. 27, 6591-6597 (2015).

[16] . Singh, M., Kaiser, J. & Hahn, H. Thick electrodes for high energy lithium ion batteries. J. Electrochem. Soc. 162, A1196-A1201 (2015).

[17] . Lee, B.-S. et al. Analysis of rate-limiting factors in thick electrodes for electric vehicle applications. J. Electrochem. Soc. 165, A525-A533 (2018).

[18] . Ender, M., Joos, J., Carraro, T. & Ivers-Tiffee, E. Three-dimensional reconstruction of a composite cathode for lithium-ion cells. Electrochem. Commun. 13, 166-168 (2011).

[19] . Choi, W., Lahiri, I., Seelaboyina, R. & Kang, Y. S. Synthesis of graphene and its applications: A review. Crit, Rev. Solid State 35, 52-71 (2010).

[20] . Yi, M. & Shen, Z. A review on mechanical exfoliation for the scalable production of graphene. J. Mater. Chem. A 3, 11700-11715 (2015).

[21] . Kucinskis, G., Bajars, G. & Kleperis, J. Graphene in lithium ion battery cathode materials: A review. J. Power Sources 240, 66-79 (2013).

[22] . Chabot, V. et al. A review of graphene and graphene oxide sponge: material synthesis and applications to energy and the environment. Energy Environ. Sci. 7, 1564-1596 (2014).

[23] . Zhu, N. et al. Graphene as a conductive additive to enhance the high-rate capabilities of electrospun Li 4 Ti 5 O 12 for lithium-ion batteries. Electrochim. Acta 55, 5813-5818 (2010).

[24] . Su, F.-Y. et al. Could graphene construct an effective conducting network in a high-power lithium ion battery? Nano Energy 1, 429-439 (2012).

[25] . Bi, H. et al. Study of LiFePO 4 cathode modified by graphene sheets for high-performance lithium ion batteries. Electrochim. Acta 88, 414-420 (2013).

[26] . Belyaeva, L. A., van Deursen, P. M. G., Barbetsea, K. I. & Schneider, G. F. Hydrophilicity of graphene in water through transparency to polar and dispersive interactions. Adv. Mater. 30, 1703274 (2018).

[27] . Li, Z. et al. Effect of airborne contaminants on the wettability of supported graphene and graphite. Nat. Mater. 12, 925-931 (2013).

[28] . Liang, Y. T. & Hersam, M. C. Highly concentrated graphene solutions via polymer enhanced solvent exfoliation and iterative solvent exchange. J. Am. Chem. Soc. 132, 17661-17663 (2010).

[29] . Kim, J. et al. Graphene oxide sheets at interfaces. J. Am. Chem. Soc. 132, 8180-8186 (2010).

[30] . Kim, J.-W., Lee, D., Shum, H. C. & Weitz, D. A. Colloid surfactants for emulsion stabilization. Adv. Mater. 20, 3239-3243 (2008).

[31] . Aggour, Y. A. Thermal decomposition behaviour of ethyl cellulose grafted copolymers in homogeneous media. J. Mater. Sci. 35, 1623-1627 (2000).

[32] . Nan, H. Y. et al. The thermal stability of graphene in air investigated by Raman spectroscopy. J. Raman Spectrosc. 44, 1018-1021 (2013).

[33] . Secor, E. B. et al. Enhanced conductivity, adhesion, and environmental stability of printed graphene inks with nitrocellulose. Chem. Mater. 29, 2332-2340 (2017).

[34] . Qiu, X.-Y. et al. Reprint of “Investigation of layered LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 cathode of lithium ion battery by electrochemical impedance spectroscopy”. J. Electroanal. Chem. 688, 393-402 (2013).

[35] . Du, K., Huang, J., Cao, Y., Peng, Z. & Hu, G. Study of effects on LiNi 0.8 Co 0.15 Al 0.05 O 2 cathode by LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 coating for lithium ion batteries. J. All. Compd. 574, 377-382 (2013).

[36] . Lee, M.-J. et al. The role of nanoscale-range vanadium treatment in LiNi 0.8 Co 0.15 Al 0.05 O 2 cathode materials for Li-ion batteries at elevated temperatures. J. Mater. Chem. A 3, 13453-13460 (2015).

[37] . Sharifi-Asl, S. et al. Anti-oxygen leaking LiCoO 2 . Adv. Funct. Mater. 29, 1901110 (2019).

[38] . Zheng, H., Li, J., Song, X., Liu, G. & Battaglia, V. S. A comprehensive understanding of electrode thickness effects on the electrochemical performances of Li-ion battery cathodes. Electrochim. Acta 71, 258-265 (2012).

[39] . Liu, M.-H., Jen, C.-W., Chen, J.-M. & Liao, S.-C. Improved electrochemical performance of Ni-rich cathode materials via Al gradient doping. Int. J. Electrochem. Sci. 13, 4350-4366 (2018).

[40] . Vu, D.-L., Choi, J.-Y., Kim, W.-B., Lee, J. J. & Lee, J.-W. Layered LiNi 0.8 Co 0.1 Mn 0.1 O 2 prepared through calcination in air with preoxidized precursor. J. Electrochem. Soc. 164, A2670-A2676 (2017).

[41] . Zheng, J., Kan, W. H. & Manthiram, A. Role of Mn content on the electrochemical properties of nickel-rich layered LiNi 0.8-x Co 0.1 Mn 0.1+x O 2(0.0≦x≦0.08) cathodes for lithium-ion batteries. ACS Appl. Mater. 7, 6926-6934 (2015).

[42] . Yoon, S. et al. Method of preparation for particle growth enhancement of LiNi 0.8 Co 0.15 Al 0.05 O 2 . Electrochem. Solid State Lett. 12, A211-A214 (2009).

[43] . Liang, M. et al. Improved performances of LiNi 0.8 Co 0.15 Al 0.05 O 2 material employing NaAlO 2 as a new aluminum source. ACS Appl. Mater. 9, 38567-38574 (2017).

[44] . Vu, D.-L. & Lee, J.-w. Properties of LiNi 0.8 Co 0.1 Mn 0.1 O 2 as a high energy cathode material for lithium-ion batteries. Korean J. Chem. Eng. 33, 514-526 (2016).

[45] . Wu, G. & Zhou, Y. TiP 2 O 7 -coated LiNi 0.8 Co 0.15 Al 0.05 O 2 cathode materials with improved thermal stability and superior cycle life. J. Energy Chem. 28, 151-159 (2019).

[46] . Zhamu, A. et al., Graphene-enhanced cathode materials for lithium batteries, US8691441B2, (2010).

[47] . Zhamu, A. et al., Nano graphene reinforced nanocomposite particles for lithium battery electrodes, US20100143798A1, (2008).

[48] . Adamson, D. H. et al., Graphene / graphite polymer composite foam derived from emulsions stabilized by graphene / graphite kinetic trapping, WO2015184155A1, (2015).

[49] . Miller, S.A., Coating a substance with graphene, US8691335B2, (2010).

[50] . Mao, Z & Chahar, B., Carbon-coated silicon particle power as the anode material for lithium ion batteries and the method of making the same, EP1702375B1, (2003).

[51] . Mo, R. et al., Facile synthesis of nanocrystalline LiFePO 4 / graphene composite as cathode material for high power lithium ion batteries, Electrochimica Acta, 130, 594-599, (2014).

[52] . Li, N et al., The preparation and graphene surface coating NaTi 2 (PO4 ) 3 as cathode material for lithium ion batteries, Applied Surface Science, 399, 624-629, (2017).

[53] . Chen, K. et al., Comprehensive Enhancement of Nanostructured Lithium-Ion Battery Cathode Materials via Conformal Graphene Dispersion, Nano Letters, 17, 4, 2539-2546, (2017).

Claims

1. 1. A method for producing a composite material, comprising: forming an emulsion mixture of active material particles and graphene emulsion droplets containing immiscible first and second solvents and a graphene solid state emulsifier, the first and second solvents being matched such that the first solvent is an external solvent and the second solvent is present inside the graphene emulsion droplets and the active material particles are present inside the emulsion droplets, the boiling point of the second solvent being lower than the boiling point of the first solvent; drying the emulsion mixture, followed by evaporating the second solvent and the first solvent by fractional distillation to form a composite material in which each surface of the active material particles is conformally coated with the graphene; Including, The graphene emulsion droplets further contain ethyl cellulose (EC) as an additive to enhance the dispersibility and emulsifier properties of the graphene.

2. said step of forming an emulsion mixture further comprising: dispersing the graphene in a first solvent to form a base solution; mixing a second solvent with the base solution to form graphene emulsion droplets by ultrasonic treatment; inserting the active material particles into the graphene emulsion droplets by stirring; The method of claim 1 , comprising:

3. said step of forming an emulsion mixture further comprising: dispersing the graphene in a first solvent to form a base solution; dispersing active material particles in a base solution to form a first mixture; adding a second solvent to the first mixture to form a second mixture and sonicating the second mixture to intercalate the active material particles into the graphene emulsion droplets; The method of claim 1 , comprising:

4. 4. The method of claim 3, wherein the mass ratio of the graphene to the EC ranges from 1:0 to 1:

3.

5. The method further comprises the step of thermally annealing the composite material in an oxidizing environment at a temperature to decompose most of the EC, and the remaining amorphous carbon residue is converted into sp 2 The method of claim 3 comprising carbon.

6. The method of claim 5, wherein the temperature is in the range of 150 to 350° C.

7. 10. The method of claim 1, wherein the average size of the graphene emulsion droplets is varied by varying the volume ratio of a first solvent to a second solvent and the concentration of the graphene in the base solution.

8. 2. The method of claim 1, wherein the volume ratio of the first solvent to the second solvent ranges from 5:4 to 5:

1.

9. 9. The method of claim 8, wherein the average size of the graphene emulsion droplets decreases with decreasing content of the second solvent and is less than 5 μm at a volume ratio of the first solvent to the second solvent of 5:

1.

10. 10. The method of claim 1, wherein the first solvent comprises acetonitrile, heptane, water, or acetic acid, and the second solvent comprises pentane, cyclohexane, acetonitrile, benzene, hexane, or chloroform.

11. 10. The method of claim 1, wherein the first solvent comprises acetonitrile having a boiling point of 82°C and the second solvent comprises hexane having a boiling point of 68°C.

12. 12. The method of claim 11 , wherein the fractional distillation is carried out in a rotary evaporator with a bath temperature set at 50° C. and a pressure set at 0.6 atm for a first period of time to completely and selectively remove the hexane, thereby resulting in a controlled collapse of the emulsion droplets and a conformal graphene coating on the active material particles, and subsequently the pressure is reduced to less than 0.2 atm for a second period of time to completely remove the acetonitrile, thereby resulting in conformal graphene-coated active material particles.

13. 2. The method of claim 1, wherein the mass ratio of the graphene to active material particles is in the range of 1:400 to 1:

100.

14. The method of claim 1 , wherein the graphene comprises solution exfoliated graphene.

15. 10. The method of claim 1, wherein the active material comprises lithium cobalt oxide, lithium iron phosphate, lithium manganese oxide, lithium nickel manganese cobalt oxide, lithium nickel cobalt aluminum oxide, or combinations thereof.

16. The method of claim 15 , wherein the active material comprises nickel-rich lithium oxide.

17. The active material is LiNi 0.8 Co 0.15 A 0.05 O 2 (NCA), LiNiO 2 (LNO), LiMn 1.5 Ni 0.5 O 4 (LMNO), LiNi x Mn y Co z O 2 (NMC, where x+y+z=1), LiNi 0.8 Co 0.2 O 2 (LNCO), or Li w Ni x Mn y Co z O 2 17. The method of claim 16, comprising: (lithium-rich NMC, where w>1 and x+y+z=1).

18. 18. The method of claim 17, wherein the active material is doped with an element comprising Al, B, Zr, Nb, Fe, Cr, Cu, Mo, W, and / or V.

19. Graphene and Active material particles and Amorphous carbon with sp 2 carbon to promote electron transport between graphene flakes and A composite material comprising: each surface of an active material particle is conformally coated with the graphene; The amorphous carbon is an annealing product of ethyl cellulose; Composite material.

20. 20. The composite material of claim 19, wherein the mass ratio of the graphene to active material particles is in the range of 1:400 to 1:

100.

21. 20. The composite material of claim 19, wherein the graphene comprises solution exfoliated graphene.

22. 20. The composite material of claim 19, wherein the active material comprises lithium cobalt oxide, lithium iron phosphate, lithium manganese oxide, lithium nickel manganese cobalt oxide, lithium nickel cobalt aluminum oxide, or a combination thereof.

23. 23. The composite material of claim 22, wherein the active material comprises nickel-rich lithium oxide.

24. The active material is LiNi 0.8 Co 0.15 A 0.05 O 2 (NCA), LiNiO 2 (LNO), LiMn 1.5 Ni 0.5 O 4 (LMNO), LiNi x Mn y Co z O 2 (NMC, where x+y+z=1), LiNi 0.8 Co 0.2 O 2 (LNCO), or Li w Ni x Mn y Co z O 2 24. The composite material of claim 23 comprising: lithium-rich NMC, where w>1 and x+y+z=1.

25. 25. The composite material of claim 24, wherein the active material is doped with an element comprising Al, B, Zr, Nb, Fe, Cr, Cu, Mo, W, and / or V.

26. An electrode for an electrochemical device, comprising: a composite material including graphene, active material particles, and amorphous carbon having sp 2 carbon that facilitates electron transport between the graphene flakes, wherein each surface of the active material particles is conformally coated with the graphene; An electrode, wherein the amorphous carbon is an annealing product of ethyl cellulose.

27. 27. The electrode of claim 26, wherein the mass ratio of the graphene to active material particles is in the range of 1:400 to 1:

100.

28. 27. The electrode of claim 26, wherein the graphene comprises solution exfoliated graphene.

29. 27. The electrode of claim 26, wherein the active material comprises lithium cobalt oxide, lithium iron phosphate, lithium manganese oxide, lithium nickel manganese cobalt oxide, lithium nickel cobalt aluminum oxide, or combinations thereof.

30. 30. The electrode of claim 29, wherein the active material comprises nickel-rich lithium oxide.

31. The active material is LiNi 0.8 Co 0.15 A 0.05 O 2 (NCA), LiNiO 2 (LNO), LiMn 1.5 Ni 0.5 O 4 (LMNO), LiNi x Mn y Co z O 2 (NMC, where x+y+z=1), LiNi 0.8 Co 0.2 O 2 (LNCO), or Li w Ni x Mn y Co z O 2 31. The electrode of claim 30 comprising lithium-rich NMC, where w>1 and x+y+z=1.

32. 32. The electrode of claim 31 , wherein the active material is doped with an element comprising Al, B, Zr, Nb, Fe, Cr, Cu, Mo, W, and / or V.

33. Electrodes with as little as 0.5% by mass of graphene can achieve a capacity of 10 mg cm -2 27. The electrode of claim 26, wherein the electrode achieves greater than about 100% active material area loading, and volumetric and specific capacitances of at least 98% of the theoretical limits of the active material.

34. 34. The electrode of claim 33, wherein an electrode having as little as 0.5% by weight of graphene retains 91.5% of its initial volumetric capacity over 100 cycles and maintains a coulombic efficiency of 99.7%.

35. 35. The electrode of claim 34, wherein an electrode having as little as 0.5% by weight of graphene retains 70% of its initial volumetric capacity over 250 cycles.

36. 27. An electrochemical device comprising the electrode of claim 26.

37. 37. The electrochemical device of claim 36 which is a battery.

Citation Information

Patent Citations

  • Lithium-rich nickel manganese cobalt oxide (LR-NMC)

    JP2018505521A

  • Nanostructured Lithium-ion Battery Electrode Composites with Conformal Graphene Dispersion

    JP2020508541A